AMERICAN LITERATURE AT THE TURN OF THE TWENTIETH CENTURY: TRANSITION, INNOVATION, AND CULTURAL IDENTITY - Iroda Egamberdiyeva Abdurahimovna,; Najimov Dilshodbek Hasanboy o‘g‘li, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article explores the transformation of American literature at the turn of the twentieth century, a period marked by significant social, cultural, and artistic change. The  study  examines  how  literary  movements  evolved  during  this  transitional  era, moving from realism and naturalism toward modernism. Particular attention is given to the ways in which writers responded to industrialization, urbanization, and shifting cultural values. The research highlights the contributions of authors such as Henry James, Theodore Dreiser, and Edith Wharton, whose works reflect both continuity and innovation in literary forms. Their writings reveal the tensions between tradition and change, as well as the emergence of new narrative techniques and thematic concerns. Furthermore,  the  article  argues  that  this  period  played  a  crucial  role  in  shaping American  cultural  identity.  Literature  became  a  medium  through  which  writers explored  issues  of  class,  gender,  and  individual  consciousness,  contributing  to  the development of a distinct national voice in the global literary landscape.